Beginning Java SE 6 Platform - Friesen, Jeff (Apress, 2012)
This book starts you on a journey of exploration into most of Java SE 6’s new and improved features. Unfortunately, various constraints kept me from covering every feature, including the JavaBeans Activation Framework (<<sigh>>). While you learn about these features, you’ll also encounter exciting technologies, such as JRuby and JavaFX, and even catch a glimpse of Java SE 7. You’ll also find numerous questions and exercises that challenge your understanding of Java SE 6, and numerous links to web resources for continuing this journey. Beginning Java SE 6 Platform is a must-have resource if you want to quickly upgrade your skills. It is also the right choice if you need information about performance and other important topics before deciding if your company should upgrade to Java SE 6. This book will save you from wading through Java SE Development Kit (JDK) documentation and performing a lot of Internet searches.